2013
DOI: 10.1111/jcmm.12134
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes express PDGFRα in the human gastrointestinal tract

Abstract: Telocytes (TC), a cell population located in the connective tissue of many organs of humans and laboratory mammals, are characterized by a small cell body and extremely long and thin processes. Different TC subpopulations share unique ultrastructural features, but express different markers. In the gastrointestinal (GI) tract, cells with features of TC were seen to be CD34-positive/c-kit-negative and several roles have been proposed for them. Other interstitial cell types with regulatory roles described in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
235
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(277 citation statements)
references
References 54 publications
38
235
3
1
Order By: Relevance
“…Moreover, in this study, and in several others, it was demonstrated that none of the CD34 and PDGFRα + cells were c-Kit labeled, definitively excluding that these cells are ICC (50)(51)(52)(53)(54)(55) (Figure 4). Notably, while in these reports (54,55) some cells located in the axes of the villi were PDGFRα + , Vannucchi et al (51) could not find any CD34 positive cells at this level. Under TEM, cells with the features of TC were described in the axes of the villi and called myoid cells (56)(57)(58).…”
Section: Tc Identification By Immunohistochemistry (See Table 1)mentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, in this study, and in several others, it was demonstrated that none of the CD34 and PDGFRα + cells were c-Kit labeled, definitively excluding that these cells are ICC (50)(51)(52)(53)(54)(55) (Figure 4). Notably, while in these reports (54,55) some cells located in the axes of the villi were PDGFRα + , Vannucchi et al (51) could not find any CD34 positive cells at this level. Under TEM, cells with the features of TC were described in the axes of the villi and called myoid cells (56)(57)(58).…”
Section: Tc Identification By Immunohistochemistry (See Table 1)mentioning
confidence: 88%
“…Recently, by using the PDGFRα antibody, cells sharing the same distribution of the CD34 positive cells were identified (51)(52)(53)(54)(55). The PDGF/PDGF receptor signaling pathway plays critical roles in mammalian organogenesis and murine GI villous morphogenesis, and it has been demonstrated that selective inhibition of the PDGFR suppresses longitudinal smooth muscle differentiation (53).…”
Section: Tc Identification By Immunohistochemistry (See Table 1)mentioning
confidence: 99%
“…Thus, the stromal cells we describe display characteristics typical of TCs, both morphologically and immunophenotypically. In fact, TCs are characterized by a nucleated body (whose shape varies from small oval to triangular/polygonal or large round‐to‐oval, depending on the TCs’ anatomical location) that branches out into extremely long and thin prolongations, called “telopodes”; moreover, CD34 and PDGFRA are currently considered the most reliable markers for their immunohistochemical identification 24, 29. Additionally, the cells we describe are clearly distinguishable from ICCs because of both their immunophenotype and their compartmentalization.…”
Section: Discussionmentioning
confidence: 99%
“…Double immunofluorescence staining combining CD34 either with PDGFRα or c‐kit/CD117 was performed according to previously published studies 31, 32, 43. Paraffin‐embedded corneal tissue sections (5 μm thick) were deparaffinized, rehydrated and boiled for 10 min.…”
Section: Methodsmentioning
confidence: 99%